Analytical Impedance Spectroscopy: Basics and Applications - Pandey L.; Kumar D.; Parkash O.; Pandey S. (My University, 2025)
This book introduces the subject of impedance spectroscopy starting from fundamentals through to latest applications in areas such as ceramics, piezoelectric, sensors, agriculture, food quality control, medical diagnostics, cancer research, and so forth. Within the ambit of impedance spectroscopy, plots simulated for useful equivalent circuit models, design of sample holder, necessary precautions to be taken during measurement are described. It further discusses development of softwares for analysis of experimental data and choice of the most appropriate equivalent circuit model. All the materials are supported by problems, answers, appendices and references. Features: Includes fundamentals, equivalent circuit modeling and analysis of data related to impedance spectroscopy. Presents experimental measurements in a nuts-and-bolts approach. Includes derivation of expressions for some selected models and values of immittance functions as frequency of measurements tend to zero and to infinity. Provides clear recipe for beginners for proceeding toward developing equivalent circuit models. Describes computer program for complex nonlinear least squares fitting with example of program IMPSPEC.BAS This book is aimed at senior undergraduate/graduate students and researchers in materials engineering, mechanical engineering, electrical engineering, chemical engineering, biomedical engineering, construction engineering, physics, chemistry, medical diagnostics, agriculture and dairy. © 2024 Lakshman Pandey, Devendra Kumar, Om Parkash and Shukdev Pandey.